2018
DOI: 10.1021/acs.jced.8b00451
|View full text |Cite
|
Sign up to set email alerts
|

Isobaric Vapor–Liquid Equilibrium of Furfural + γ-Valerolactone at 30 kPa and Isothermal Liquid–Liquid Equilibrium of Carbon Dioxide + γ-Valerolactone + Water at 298 K

Abstract: The phase equilibria of four subsystems related to the γ-valerolactone (GVL) based biorefinery concept were measured. The liquid−liquid equilibrium (LLE) is important in separating GVL from aqueous solution with the aid of carbon dioxide. LLE of dense carbon dioxide, GVL, and water at 7.5 MPa was measured in a high pressure equilibrium cell equipped with a pneumatic capillary sampler. The solubility of GLV was from 2 to 10 times higher in the dense CO 2 phase than in the aqueous phase indicating CO 2 is a good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 40 publications
3
16
0
Order By: Relevance
“…It was earlier shown that GVL does not form a measurable amount of peroxide under air and does not make an azeotropic mixture with water, C 1 –C 3 alcohols and formic acid . Its temperature-dependent vapor pressure as a key property even in the case of solvent utilization was recently measured by several groups. , Pokki and co-workers determined the isobaric vapor–liquid equilibrium (VLE) data of the GVL–furfural system and investigated the GVL–water binary mixture including its isothermal VLE data, the excess enthalpy, and density of aqueous GVL solutions . Růžička measured the enthalpy of vaporization and fusion as well as condensed phase heat capacity of GVL .…”
Section: Introductionmentioning
confidence: 99%
“…It was earlier shown that GVL does not form a measurable amount of peroxide under air and does not make an azeotropic mixture with water, C 1 –C 3 alcohols and formic acid . Its temperature-dependent vapor pressure as a key property even in the case of solvent utilization was recently measured by several groups. , Pokki and co-workers determined the isobaric vapor–liquid equilibrium (VLE) data of the GVL–furfural system and investigated the GVL–water binary mixture including its isothermal VLE data, the excess enthalpy, and density of aqueous GVL solutions . Růžička measured the enthalpy of vaporization and fusion as well as condensed phase heat capacity of GVL .…”
Section: Introductionmentioning
confidence: 99%
“…The rate of GVL removal from the spent liquor decreased as the extraction proceeded, because the partition coefficient approached unity at low GVL concentration. 27 Moreover, the lack of a mixing mechanism in our system severely limited the mass transfer of GVL to the CO 2 phase. Both phenomena resulted in a high leftover GVL rate (∼10%) in the raffinate, even at excessive CO 2 dosage.…”
Section: Resultsmentioning
confidence: 99%
“… 25 , 26 Our parallel study on the thermodynamics and phase behaviors of the GVL–CO 2 –water ternary system confirmed the affinity of GVL toward the CO 2 phase over the aqueous phase at room temperature and high pressure. 27 These two separation methods served as the core techniques of our recovery schemes.…”
Section: Introductionmentioning
confidence: 99%
“…This publication is available free of charge from: https://doi.org/10.6028/NIST.IR.8357 Triangles are for 2-furaldehyde + furfuryl alcohol: , Myles and Wingard [46]; , Tsirlin and Vasil'eva [47]. Diamonds () are for 2-furaldehyde + γ-valerolactone, Pokki et al [48]. Squares () are for 2-furaldehyde + 2-acetylfuran, Zheng et al [49].…”
Section: Vle Of Two Furan Derivativesmentioning
confidence: 99%